2023
DOI: 10.1097/pxr.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket costs and affordability of upper limb prostheses

Abstract: Background: Given the funding policies in the Department of Veterans Affairs, the affordability of prostheses may be less of a concern among Veterans as compared to civilians. Objectives: Compare rates of out-of-pocket prosthesis-related payments for Veterans and non-Veterans with upper limb amputation (ULA), develop and validate a measure of prosthesis affordability, and evaluate the impact of affordability on prosthesis nonuse. Study design: Telephone survey of 727 persons with ULA; 76% Veterans and 24% non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The survey included demographic questions related to sex, Veteran status, race, and ethnicity. It also included the Trinity Amputee Prosthetic Evaluation Scale (TAPES)-Upper prosthesis satisfaction measure [ 30 ], the Orthotics and Prosthetics User Survey (OPUS), Client Satisfaction with Device (CSD) scale [ 31 ], three new subscales from a revised OPUS CSD (Comfort, Appearance, Utility) [ 32 ] and additional items and measures related to psychosocial adjustment [ 33 ], activity performance [ 34 , 35 ], patient experience [ 36 ], and residual limb health [ 37 ], and prosthesis affordability [ 38 ], all reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…The survey included demographic questions related to sex, Veteran status, race, and ethnicity. It also included the Trinity Amputee Prosthetic Evaluation Scale (TAPES)-Upper prosthesis satisfaction measure [ 30 ], the Orthotics and Prosthetics User Survey (OPUS), Client Satisfaction with Device (CSD) scale [ 31 ], three new subscales from a revised OPUS CSD (Comfort, Appearance, Utility) [ 32 ] and additional items and measures related to psychosocial adjustment [ 33 ], activity performance [ 34 , 35 ], patient experience [ 36 ], and residual limb health [ 37 ], and prosthesis affordability [ 38 ], all reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…16,18 A recent study of US veterans and nonveterans with ULA found that 14% of persons who never used a prosthesis and 9.6%-16.5% of prosthesis abandoners reported that affordability was a primary reason for nonuse with veterans having 0.20 the odds of paying outof-pocket costs compared with nonveterans. 19 Unmet need for assistive technologies, including mobility devices, has been widely studied, 2 and scoping reviews on global needs for rehabilitation services and equipment 2 point to unmet need for prostheses, particularly in geographic areas affected by war, where prosthetic expertise and resources are lacking. However, no prior studies have examined the prevalence of unmet prosthesis need among persons with ULA who were not using a prosthesis.…”
mentioning
confidence: 99%
“…Others may lack access to prosthetic expertise, which varies across the United States, 3,17 or may abandon or reject prostheses because they are unable to afford the prosthesis and/or the associated costs for repair and maintenance 16,18 . A recent study of US veterans and nonveterans with ULA found that 14% of persons who never used a prosthesis and 9.6%–16.5% of prosthesis abandoners reported that affordability was a primary reason for nonuse with veterans having 0.20 the odds of paying out-of-pocket costs compared with nonveterans 19 …”
mentioning
confidence: 99%